Pregunta
upstudy study bank question image url

Find an equation of the line containing the conters of the two circles whose equations are given below. \[ \begin{array}{l} (x-4)^{2}+(y+5)^{2}=25 \\ (x+3)^{2}+(y-6)^{2}=16 \end{array} \] The general form of the equation of the line \( \square \) (Simplify your answer.)

Ask by Chadwick Marsh. in the United States
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The equation of the line is \( 11x + 7y - 9 = 0 \).

Solución

The centers of the circles are determined by the points: • First circle: (x – 4)² + (y + 5)² = 25 has center (4, –5) • Second circle: (x + 3)² + (y – 6)² = 16 has center (–3, 6) To find the line through these centers, first calculate the slope, m:   m = (6 – (–5)) / (–3 – 4) = 11 / (–7) = –11/7 Using the point-slope form with one of the centers, for example (4, –5):   y – (–5) = (–11/7)(x – 4)   y + 5 = (–11/7)(x – 4) To write in general form, first eliminate the fraction by multiplying both sides by 7:   7(y + 5) = –11(x – 4)   7y + 35 = –11x + 44 Now, rearrange terms to bring them all to one side:   11x + 7y + 35 – 44 = 0   11x + 7y – 9 = 0 Thus, the equation of the line in general form is:   11x + 7y – 9 = 0

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To find the equation of the line that contains the centers of the two circles given by the equations, we need to identify the centers of each circle. 1. For the circle \((x-4)^{2}+(y+5)^{2}=25\), the center is at \( (4, -5) \). 2. For the circle \((x+3)^{2}+(y-6)^{2}=16\), the center is at \( (-3, 6) \). Next, we find the slope \( m \) of the line that passes through these two points \((4, -5)\) and \((-3, 6)\): \[ m = \frac{y_2 - y_1}{x_2 - x_1} = \frac{6 - (-5)}{-3 - 4} = \frac{11}{-7} = -\frac{11}{7}. \] Now, we can use point-slope form to write the equation of the line. Using the point \((4, -5)\): \[ y + 5 = -\frac{11}{7}(x - 4). \] Simplifying this equation: \[ y + 5 = -\frac{11}{7}x + \frac{44}{7}. \] Subtract 5 (which is \(\frac{35}{7}\)) from both sides: \[ y = -\frac{11}{7}x + \frac{44}{7} - \frac{35}{7} = -\frac{11}{7}x + \frac{9}{7}. \] To express this in general form, multiply every term by 7: \[ 7y = -11x + 9. \] Rearranging gives: \[ 11x + 7y - 9 = 0. \] Thus, the general form of the equation of the line is: \[ \boxed{11x + 7y - 9 = 0}. \]

preguntas relacionadas

Latest Geometry Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad